2018
DOI: 10.1021/acs.langmuir.8b00492
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Osmotic Swelling in Highly Charged Clay Minerals

Abstract: Delamination by osmotic swelling of layered materials is generally thought to become increasingly difficult, if not impossible, with increasing layer charge density because of strong Coulomb interactions. Nevertheless, for the class of 2:1 layered silicates, very few examples of delaminating organo-vermiculites were reported in literature. We propose a mechanism for this repulsive osmotic swelling of highly charged vermiculites based on repulsive counterion translational entropy that dominates the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 48 publications
0
64
0
Order By: Relevance
“…The fluorohectorite [Na 0.5 ][Li 0.5 Mg 2.5 ][Si 4 ]O 10 F 2 NSs used have a high aspect ratio of ~20,000 and a charge density of 1.1 nm −2 , enabling repulsive osmotic delamination into single lamellae in water (Supplementary Fig. 1 ) 31 , 32 . The aqueous suspension of NSs forms a homogeneous liquid crystalline phase at a very low content, C NS , of 0.3 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorohectorite [Na 0.5 ][Li 0.5 Mg 2.5 ][Si 4 ]O 10 F 2 NSs used have a high aspect ratio of ~20,000 and a charge density of 1.1 nm −2 , enabling repulsive osmotic delamination into single lamellae in water (Supplementary Fig. 1 ) 31 , 32 . The aqueous suspension of NSs forms a homogeneous liquid crystalline phase at a very low content, C NS , of 0.3 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…The delamination and subsequent exfoliation of clay nanolayers, i.e. the two-step process of physically obtaining the situation depicted in Figure 4a starting from the situation depicted in Figures 4b and 4c is most often performed in aqueous suspension, and in this case, the two-step process is referred to as attractive crystalline and osmotic swelling respectively [32][33][34]. This delamination process can be promoted by sonification or by temperature ( Fig.…”
Section: Fig 2 Adopted From Supplementary Informationmentioning
confidence: 99%
“…Very much like exfoliated GO in aqueous suspension [67,68], exfoliated clay nanolayers in aqueous suspension form entropically driven nematic phases [13,33,34,[69][70][71][72][73]] merely due to their individual platelet shape and thus loss of rotational degrees of freedom. It has been found that also clay particle stacks form nematic phases [14,[74][75][76][77][78] independently of delamination and exfoliation, since also the full particles are platelet shaped, although much thicker than the individual nanolayers.…”
Section: Fig 2 Adopted From Supplementary Informationmentioning
confidence: 99%
“…Consequently, it is most efficient and material‐saving to apply fillers with the highest aspect ratio accessible and at the maximum filler level that can be processed . Melt synthesized hectorites come in diameters of up to 20 µm and moreover can be utterly delaminated into 1 nm thick nanosheets by repulsive osmotic swelling simply by immersing them into water . The suspensions obtained represent viscous liquid crystalline (nematic) phases because the huge aspect ratio blocks isotropic rotation .…”
Section: Introductionmentioning
confidence: 99%
“…[20] Melt synthesized hectorites come in diameters of up to 20 µm and moreover can be utterly delaminated into 1 nm thick nanosheets by repulsive osmotic swelling simply by immersing them into water. [4,[21][22][23] The suspensions obtained represent viscous liquid crystalline (nematic) phases because the huge aspect ratio blocks isotropic rotation. [24][25][26] The nematic phases can, however, easily be mixed with watersoluble polymers without triggering any reaggregation.…”
mentioning
confidence: 99%